From Multilatina to Global Latina: Unveiling the corporate-level international strategy choices of Grupo Nutresa (2016)
Research on Multilatinas has underexplored multinationals from Colombia and their corporate-level international strategy choices to develop into Global Latinas. Building on interviews, documents, and archival data about Grupo Nutresa –Colombia’s most international firm in manufactured goods–, this study unveils and discusses this firm’s corporate-level international strategy choices between 1960 and 2014. A prevailing notion is that most multinationals from Latin America continue to target international operations to focus mainly on their home region through an export, multidomestic or transnational corporate-level international strategy. In contrast, data show that Grupo Nutresa chose to evolve through a sequential approach from an export to a transnational corporate-level international strategy while its international operations were able to transcend its home region to reach North America, Asia, Europe, Africa, and Oceania. These results add to international business research on emergent market multinational companies (EMNCs) from Latin America by unveiling the corporate-level international strategy choices of a Colombian origin Multilatina that transformed into a Global Latina.